A novel accuracy model for the intrinsic kinematic property of a prismatic pair. (August 2018) - Wu, Yu; Wang, Zhi; Dong, Huimin; Wang, Delun
A novel accuracy model is proposed to analyze the intrinsic kinematic property of the prismatic pair. The geometric error of guide rails, the elastic constrained structure of moving joints, and fixed joints are considered synthetically. The geometric error is measured by the 5D laser interferometer system with slide blocks. The elastic moving joints are equivalent to the springs, while the fixed joints to contact layers. The equilibrium equations are then set up and the analytical solution for five degrees-of-freedom errors of the moving table is revealed. The global invariant errors, including the straightness error space and the spherical image error surface, are proposed to describe the global kinematic characteristic of the moving table. Along with the comparison between the measured and theoretical indicators, the verification experiment to prove the availability of the model is carried out. As the movement of the table can be forecast precisely and evaluated objectively, the new methodology provides a theoretical basis for machine tool manufacture.